The legal Nature of the Virtual Currency: In-Depth Legal Insight - Al-Majali, Ahmed (UAEU Law Journal, 2023)

The Extent to which a Contract may be Terminated Based on a Prior Breach of the Contractual Obligation: A Comparative Study - Adwan, Mohdkhair; Otoum, Naim (UAEU Law Journal, 2023)
The Contractual Obligation is proven to be owed by its owner as soon as the contract is concluded or the deadline for its implementation is due, Following this that the contractual violation should be before it not after, and if that kind of violation is the ordinary kind of contractual fault so the happening of contractual violation before the execution is a case been put by rules and Judicial Pronouncements as putting it in certain ordered law firm has its special private rules and obligations that distinguishes it from any similar cases of the expiry of contract. And for that the advanced breaching by any behavior came out of the debtor in a clear or hidden way makes it Impossible or in-vain to execute a future commitment, because of that there will be a serious average on the creditor that that allows him to revoke the contract or ending it or asking for the compensation of any average might be caused by the debtor. The Arabic laws haven’t exclusive a special law for that hidden violation regardless how important it is, and amongst the warnings of going to the ordinary law of handling the wrongs of contractual violations specially with the hidden contractual commitments regarding the typical dissonance with the normal known violation.

Criteria for Considering the Shari’a Need when Applied to a Commercial Insurance Contract: An Applied Jurisprudential Study - Al-Shafei, Ahmed (UAEU Law Journal, 2023)
control and measure it. By proposing a list of criteria used in assessing their existence, consideration or elimination, and to test the criteria, the researcher applied them to a commercial insurance. In order to achieve the goal of the research; the researcher used the inductive analytical method, by following the rules suggested by the Fuqaha’, which required an analysis of some Fuqaha’ sayings, to build standards. The research concluded that the «Need» that some Fuqaha’ considered in the permissibility of commercial insurance does not meet these criteria in a way that supports their opinion. Accordingly; Commercial insurance in its current form is not permissible, which is the opinion of the majority of contemporary Fuqaha’. The research recommends calibration what accepts calibration from the fundamentalist tools, which enable the mujtahid and the researcher to stand on the Shari’a ruling in a disciplined manner, and reduce the difference between the mujtahidin’s considerations of the tools and methods of ruling making.